EVALUATION OF EARLY CHILDHOOD EDUCATION MODELS IN UZBEKISTAN - Tomashpayeva, Sabina; Karimsakov, Timur (Nazarbayev University Graduate School of Public Policy, 2024)
This study evaluates UNICEF-supported alternative Early Childhood Education (ECE) models in Uzbekistan, addressing challenges in access, equity, and quality of preschool education. The research hypothesizes that these models significantly improve coverage, accessibility, and quality standards, particularly for children from disadvantaged backgrounds. Using a mixed-methods approach, the study integrates quantitative and qualitative data to assess the effectiveness, scalability, and sustainability of these alternative models. Data collection included interviews with teachers, surveys with parents, and a review of national policies and administrative records. Findings indicate that the alternative ECE centers effectively increased enrollment among marginalized groups and improved children’s readiness for school, meeting the national Early Learning Development Standards (ELDS). However, challenges such as teacher retention, inconsistent training, and resource constraints impact the program's scalability and long-term sustainability. The study highlights the importance of addressing systemic disparities in preschool education and provides actionable recommendations to improve service delivery. These include standardizing teacher training, enhancing monitoring systems, and developing mechanisms to ensure financial and operational sustainability. By addressing these gaps, UNICEF and the Government of Uzbekistan can further strengthen ECE programs to ensure equitable access and high-quality education for all children.
Keywords: Early Childhood Education; equity; accessibility; teacher training; sustainability; alternative models; Uzbekistan.; Type of access: Embargo